Does Workplace Bullying Affect Long-Term Sickness Absence Among Coworkers?. Issue 2 (February 2018) - Hansen, Åse Marie; Grynderup, Matias Brødsgaard; Bonde, Jens Peter; Conway, Paul Maurice; Garde, Anne Helene; Kaerlev, Linda; Kolstad, Henrik A.; Mikkelsen, Sigurd; Rugulies, Reiner; Thomsen, Jane Frølund; Willert, Morten; Hogh, Annie
Abstract : Aim: To examine if non-bullied employees at work units (WUs) with workplace bullying have more long-term sickness absence (LTSA) than employees in non-bullying WUs. Methods: We included 7229 public health employees from 302 WUs and 3158 responders to a questionnaire on working conditions and health in 2007. WUs were classified into three categories of WUs; (1) no bullying (0% bullied); (2) moderate prevalence of bullying (less than 10% bullied); and (3) high prevalence of bullying (more than or equal to 10% bullied). LTSA (more than or equal to 30 consecutive days of sickness absence) during the following 2 years was obtained by linkage to the Danish register of sickness absence compensation benefits and social transfer payments. Results: Non-bullied coworkers in WUs, where bullying was reported had 15% to 22% more LTSA compared with non-bullying WUs. Conclusion: Workplace bullying may be associated with LTSA in the entire WU.